The Mediterranean diet, plasma metabolome, and cardiovascular disease risk. (14th May 2020) - Li, Jun; Guasch-Ferré, Marta; Chung, Wonil; Ruiz-Canela, Miguel; Toledo, Estefanía; Corella, Dolores; Bhupathiraju, Shilpa N; Tobias, Deirdre K; Tabung, Fred K; Hu, Jie; Zhao, Tong; Turman, Constance; et al.
Abstract: Aims: To investigate whether metabolic signature composed of multiple plasma metabolites can be used to characterize adherence and metabolic response to the Mediterranean diet and whether such a metabolic signature is associated with cardiovascular disease (CVD) risk. Methods and results: Our primary study cohort included 1859 participants from the Spanish PREDIMED trial, and validation cohorts included 6868 participants from the US Nurses' Health Studies I and II, and Health Professionals Follow-up Study (NHS/HPFS). Adherence to the Mediterranean diet was assessed using a validated Mediterranean Diet Adherence Screener (MEDAS), and plasma metabolome was profiled by liquid chromatography-tandem mass spectrometry. We observed substantial metabolomic variation with respect to Mediterranean diet adherence, with nearly one-third of the assayed metabolites significantly associated with MEDAS (false discovery rate   <   0.05). Using elastic net regularized regressions, we identified a metabolic signature, comprised of 67 metabolites, robustly correlated with Mediterranean diet adherence in both PREDIMED and NHS/HPFS ( r  = 0.28–0.37 between the signature and MEDAS; P  =   3 × 10 −35 to 4 × 10 −118 ). In multivariable Cox regressions, the metabolic signature showed a significant inverse association with CVD incidence after adjusting for known risk factors (PREDIMED: hazard ratio [HR] per standard deviation increment in the signature = 0.71, P  <   0.001; NHS/HPFS: HR = 0.85, P  =   0.001), and the association persisted after further adjustment for MEDAS scores (PREDIMED: HR = 0.73, P  =   0.004; NHS/HPFS: HR = 0.85, P  =   0.004). Further genome-wide association analysis revealed that the metabolic signature was significantly associated with genetic loci involved in fatty acids and amino acids metabolism. Mendelian randomization analyses showed that the genetically inferred metabolic signature was significantly associated with risk of coronary heart disease (CHD) and stroke (odds ratios per SD increment in the genetically inferred metabolic signature = 0.92 for CHD and 0.91 for stroke; P  <   0.001). Conclusions: We identified a metabolic signature that robustly reflects adherence and metabolic response to a Mediterranean diet, and predicts future CVD risk independent of traditional risk factors, in Spanish and US cohorts.